METHODOLOGICAL APPROACHES TO THE MANAGEMENT SYSTEM OF FREIGHT FORWARDING SERVICES - D. Abdyusheva (Вестник университета, 2018)
Methodological approaches to the management of transport and forwarding services have presented. The approaches to the organization of the management of transport and forwarding services have considered, the positions of the manufacturer, forwarder and consignee have presented. Three stages of the methodological approaches to the organization of freight-forwarding services have studied. The basic principles of freight-forwarding services, that presuppose achievement of the goals, are highlighted: an increase in labor productivity by one employee, a minimum of a time period, a decrease in enterprise costs, a maximum of company prot, synergies between partners.